Fluorinated and Un-fluorinated N-halamines as Antimicrobial and Biofilm-controlling Additives for Polymers - Lin, Jiajin (Polymer (Guildf), 2015)
The objective of this study was to evaluate the effects of fluorination on the antimicrobial and biofilm-controlling activities of N-halamine-based additives for polymers. A fluorinated N-halamine, 1-chloro-3-1H,1H,2H,2H-perflurooctyl-5,5-dimetylhydantoin (Cl-FODMH), and its un-fluorinated counterpart, 1-chloro-3-octyl-5,5-dimethylhydantoin (Cl-ODMH), were synthesized and characterized with FT-IR, (1)H-NMR, and DSC studies. Polyurethane (PU) films containing Cl-ODMH and Cl-FODMH as antimicrobial additives were fabricated through solvent casting. With the same additive contents (1wt%-5 wt%), PU films with Cl-FODMH showed higher contact angle values. AFM, SEM and DSC results revealed that while Cl-ODMH distributed evenly within PU, Cl-FODMH aggregated and formed macro-domains in PU. Antimicrobial studies showed that PU films with Cl-ODMH had higher antimicrobial and biofilm-controlling potency against Gram-positive and Gram-negative bacteria than PU samples with Cl-FODMH. These results demonstrated the importance of distribution of additives in polymers on antimicrobial performances, shedding lights on future antimicrobial material design strategies.